Effect of a multifunctional edible coating based on cassava starch on the shelf life of Andean blackberry - Misael Cortés Rodríguez; Camilo Villegas Yépez; Jesús Humberto Gil González; Rodrigo Ortega-Toro (Heliyon, 2020)
The blackberry is a fragile fruit with a high degree of decomposition, which limits its shelf life. The effect of an edible coating (EC) based on cassava starch, whey protein, beeswax, chitosan, glycerol, stearic acid, and glacial acetic acid on the shelf life of fruit stored at 4 °C was evaluated. The physical, chemical, physical, microbiological, and sensorial quality was evaluated, comparing with a fresh control fruit. The EC had a positive effect on the physicochemical and sensorial properties (mainly in texture, flavor, and aromas), due to the reduction of physiological processes, whereas the color changes are mainly due to anthocyanin losses. After 10 days of storage, weight losses were 39.6% lower and firmness was 81.4% higher; while chitosan reduced the mold and yeast count. The EC increased the useful life of the Andean blackberries by 100%.